NONLINEAR DYNAMIC CHARACTERISTIC OF THE ROTOR SUPPORTED BY FIXED-TILTING PAD JOURNAL BEARINGS - HEI Di; LV YanJun; ZHANG YongFang (Jixie qiangdu)
In this paper,the single disk flexible rotor which is supported by the fixed-tilting pad journal bearings is studied,and the model of the rotor system is established by the rotor dynamics theory. The Reynolds equation is solved by the method of Castelli based on the dynamic Reynolds equation and the boundary conditions,at the same time,the oil film force data base of single pad is established in its coordinate system. Through the coordinate transformation,the oil film force of the fixed-tiling pad journal bearing is obtained by the assembly method. When the oil film force is calculated,two situations are considered,i. e.considering the inertia of the pad and neglecting the inertia of the pad. Firstly,the comparison of the rotor orbit is complemented at the two situations. Then,the dynamic behaviors of the rotor are analyzed at the situation of considering the inertia of the pad,and the comparison of pendulum angles of tilting pads and the orbits of the rotor are implemented at different preloads and pad pivot ratios.